Causes and consequences of income inequality and the Role of institutional quality - Goh, Lim Thye (2016)
This thesis consists of five chapters aiming to empirically examine the causes and consequences of income inequality with and role of institutional quality. The first objective of this research is to investigate the effect of trade liberalisation on income inequality. Whereas, the second objective of this research seeks to explain the impact of income inequality on mental health and the third objective of this research seeks to explain the impact of income inequality on crime rates. There are two main issues motivating the first research objective of this thesis. The first,the Stolper–Samuelson theorem (1941), which argues that trade liberalisation is positively associated with income inequality, and secondly the finding of Chong and Calderon (2000), which suggests institutional quality is a significant determinant of income inequality. Alternatively, the second research objective of this thesis is motivated by four main observations beginning with the significant increases in mental illness and mental health expenditures observed worldwide (Global Burden of Diseases Study,2010). Secondly, the World Health Organisation (WHO) (2012) suggested that the external stressors that individuals deal with in everyday life, are significantly correlated with mental illness. Thirdly, the theoretical argument of income inequality hypothesis.Lastly, the suggestion of Chong and Calderon (2000) that institutional quality is a significant determinant of income inequality. The final objective of this thesis is motivated by three main observations. Firstly, the theoretical explanation of General Strain Theory (1992) on the feeling of disadvantages and unfairness, leads the poor to seek compensation and satisfaction by all means. Secondly, the influence of institutional quality on income inequality, Chong and Calderon (2000). Lastly, the reliability of future crime rate statistics is at stake (New York Times, Oct 2013).To achieve the objectives, the sample countries are being divided into three groups,namely full sample, developed and developing countries. Utilising panel system generalised method of moment (GMM) on five yearly data covering the period from 1984 to 2012 and 1989 to 2012. The empirical results of these indicate that trade liberalisation has a positive impact on income inequality. Whereas, income inequality has a positive impact on mental illness and crime rate. In addition, this thesis has also found evidence that institutional quality is associated with lower level of income inequality, mental illness and crime rate.Lastly, this thesis also provides new evidence that sheds light on the role of institutional quality as a factor influencing the impact trade liberalisation on income inequality and income inequality against mental illness and crime rate respectively. Where, the empirical results obtained demonstrate that the impact of trade liberalisation on income inequality and income inequality against mental illnes s and crime rate are conditional by the presence of institutional quality.